Improving Students Creativity in Producing Instructional Aids for Physics Lesson from Waste and Garbage - Berlianti, Nindha Ayu; Manasikana, Oktaffi Arinna; Hayati, Nur (Universitas PGRI Kanjuruhan Malang, 2019)
The rising of an environmental issue and the lack of the handling of garbage organizing give support to us to do the research by involving garbages as the main material in making simple visual aids of physics. Based on that condition, we try to make new innovations in stimulating the creativity developing of natural science education department students of UNHASY having done the lecturing of basic physics collaborated with environmental science. The purpose of the research is to be able to give insight through education program of 5R (Reduce, Reuse, Recycle, Replace, Respect) to students of natural science department of University of Hasyim Asy’ari and apply that knowledge in changing garbage to be simple visual aids of physics. The method used in this research is qualitative descriptive, whose data can be divided into 3 kinds: observation results (detail description of what has happened in the field), interview results ( direct citation from people’s statements in interview session) dan written material. The results of the data are, then analyzed by using observation sheets of creative thinking ability. The main research subjects are 29 students. Meanwhile, the research result is in the form of the average score of students’ creativity ability reaching 72.5% with high category.The rising of an environmental issue and the lack of the handling of garbage organizing give support to us to do the research by involving garbages as the main material in making simple visual aids of physics. Based on that condition, we try to make new innovations in stimulating the creativity developing of natural science education department students of UNHASY having done the lecturing of basic physics collaborated with environmental science. The purpose of the research is to be able to give insight through education program of 5R (Reduce, Reuse, Recycle, Replace, Respect) to students of natural science department of University of Hasyim Asy’ari and apply that knowledge in changing garbage to be simple visual aids of physics. The method used in this research is qualitative descriptive, whose data can be divided into 3 kinds: observation results (detail description of what has happened in the field), interview results ( direct citation from people’s statements in interview session) dan written material. The results of the data are, then analyzed by using observation sheets of creative thinking ability. The main research subjects are 29 students. Meanwhile, the research result is in the form of the average score of students’ creativity ability reaching 72.5% with high category.